Analisis Kemampuan Calon Guru dalam Menyusun Prosedur Pemecahan Masalah Fisika Materi Dinamika Rotasi dan Kesetimbangan Benda Tegar - Uzaedah, Elly; Nugroho, Sunyoto Eko; Susanto, Hadi (UPEJ Unnes Physics Education Journal, 2019)
Procedural knowledge is a factor in problem solving. In the problem solving process, expertise is needed to arrange appropriate procedures to solve a problem. The focus of this study is to determine the ability of candidate teachers in arrange problem solving procedures and knowing the relationship between the ability to arrange problem solving procedures with problem solving abilities. This study used descriptive qualitative method. Research data was obtained from written tests, interview tests and field notes. Analysis of the ability to arrange problem solving procedures using guidelines for problem solving stages according to Docktor, et.al. (2016) namely usefull description, physics approach, specification application of physics, mathematical procedures and logical progression. Based on the analysis, the ability to develop problem solving procedures for teacher candidates is divided into 3 types, namely: type 1, type 2, and type 3. The average percentage of the ability of prospective teachers in developing type 1 problem solving procedures is 51.52%, type 2 is 37.38%, and type 3 by 10.5%. In addition, the results obtained that there was no relationship between the ability to form problem solving procedures with problem solving abilities.